Poliovirus vaccination during the endgame: insights from integrated modeling - Radboud J. Duintjer Tebbens; Kimberly M. Thompson (Taylor & Francis Group, 2017)
Introduction: Managing the polio endgame requires access to sufficient quantities of poliovirus vaccines. After oral poliovirus vaccine (OPV) cessation, outbreaks may occur that require outbreak response using monovalent OPV (mOPV) and/or inactivated poliovirus vaccine. Areas covered: We review the experience and challenges with managing vaccine supplies in the context of the polio endgame. Building on models that explored polio endgame risks and the potential mOPV needs to stop outbreaks from live poliovirus reintroductions, we conceptually explore the potential demands for finished and bulk mOPV doses from a stockpile in the context of limited shelf-life of finished vaccine and time delays to convert bulk to finished vaccine. Our analysis suggests that the required size of the mOPV stockpile varies by serotype, with the highest expected needs for serotype 1 mOPV. Based on realizations of poliovirus risks after OPV cessation, the stockpile required to eliminate the chance of a stock-out appears considerably larger than the currently planned mOPV stockpiles. Expert commentary: The total required stockpile size depends on the acceptable probability of a stock-out, and increases with longer times to finish bulk doses and shorter shelf-lives of finished doses. Successful polio endgame management will require careful attention to poliovirus vaccine supplies.